Twelve months follow-up after retrograde recanalization of superficial femoral artery chronic total occlusion - Wojtasik-Bakalarz, Joanna; Arif, Salech; Chyrchel, Michał; Rakowski, Tomasz; Bartuś, Krzysztof; Dudek, Dariusz; Bartuś, Stanisław (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction : Fifty percent of cases of peripheral artery disease are caused by chronic total occlusion (CTO) of the superficial femoral artery (SFA). Ten–fifteen percent of percutaneous SFA recanalization procedures are unsuccessful. In those cases the retrograde technique can increase the success rate of the procedure, but the long-term follow-up of such procedures is still unknown. Aim : To assess the efficacy and clinical outcomes during long-term follow-up after retrograde recanalization of the SFA. Material and methods: We included patients after at least one unsuccessful percutaneous antegrade recanalization of the SFA. Patients were evaluated for the procedural and clinical follow-up of mean time 13.9 months. Results: The study included 17 patients (7 females, 10 males) who underwent percutaneous retrograde recanalization of the SFA from June 2011 to June 2015. The mean age of patients was 63 ±7 years. Retrograde puncture of the distal SFA was successful in all cases. A retrograde procedure was performed immediately after antegrade failure in 4 (23.5%) patients and after a previously failed attempt in 13 (76.5%) patients. The procedure was successful in 15 (88.2%) patients, and unsuccessful in 2 (11.8%) patients. Periprocedural complications included 1 peripheral distal embolization (successfully treated with aspiration thrombectomy), 1 bleeding event from the puncture site and 7 puncture site hematomas. During follow-up the all-cause mortality rate was 5.8% (1 patient, non-cardiac death). The primary patency rate at 12 months was 88.2% and secondary patency 100%. Conclusions : The retrograde SFA puncture seems to be a safe and successful technique for CTO recanalization and is associated with a low rate of perioperative and long-term follow-up complications.